Ranolazine for Congenital Long-QT Syndrome Type III: Experimental and Long-Term Clinical Data. (October 2016) - Chorin, Ehud; Hu, Dan; Antzelevitch, Charles; Hochstadt, Aviram; Belardinelli, Luiz; Zeltser, David; Barajas-Martinez, Hector; Rozovski, Uri; Rosso, Raphael; Adler, Arnon; Benhorin, Jesaia; Viskin, Sami
Abstract : Background—: The basic defect in long-QT syndrome type III (LQT3) is an excessive inflow of sodium current during phase 3 of the action potential caused by mutations in the SCN5A gene. Most sodium channel blockers reduce the early (peak) and late components of the sodium current ( I Na and I NaL ), but ranolazine preferentially reduces I NaL . We, therefore, evaluated the effects of ranolazine in LQT3 caused by the D1790G mutation in SCN5A . Methods and Results—: We performed an experimental study of ranolazine in TSA201 cells expressing the D1790G mutation. We then performed a long-term clinical evaluation of ranolazine in LQT3 patients carrying the D1790G mutation. In the experimental study, I NaL was significantly higher in D1790G than in wild-type channels expressed in the TSA201 cells. Ranolazine exerted a concentration-dependent block of I NaL of the SCN5A-D1790G channel without reducing peak I Na significantly. In the clinical study, among 8 patients with LQT3 and confirmed D1790G mutation, ranolazine had no effects on the sinus rate or QRS width but shortened the QTc from 509±41 to 451±26 ms, a mean decrease of 56±52 ms (10.6%; P =0.012). The QT-shortening effect of ranolazine remained effective throughout the entire study period of 22.8±12.8 months. Ranolazine reduced the QTc at all heart rates but less so during extreme nocturnal bradycardia. A type I Brugada ECG was never noticed. Conclusions—: Ranolazine blocks I NaL in experimental models of LQT3 harboring the SCN5A-D1790G mutation and shortened the QT interval of LQT3 patients. Clinical Trial Registration—: URL:https://clinicaltrials.gov ; Unique identifier: NCT01728025.